Your food - Hewitt, Sally, 1949- (London ; Franklin Watts : 2008., 2009)
Looks at the importance of choosing food that is healthy to eat and good for the planet, features brief case studies of kids who are involved in gardening, composting, and other environmentally sound food practices, and includes challenges and activities.
Includes bibliographical references (p. 31) and index.
Library Media Connection
Resource Links
4.7
3-6.
3-6
Keywords: Environmental responsibility -- Juvenile literature; Food -- Juvenile literature; Sustainable living -- Juvenile literature; Environmental responsibility; Food; Sustainable living; Food; Responsibility; Sustainable living